ANALISIS INTENSITAS MEDAN MAGNET ELF (EXTREMELY LOW FREQUENCY) DI SEKITAR PERALATAN ELEKTRONIK DENGAN DAYA ≥ 1000 W - Dhana Suhatin; Sudarti Sudarti; Trapsilo Prihandono (FKIP Universitas Jember, 2017)
Research on the analysis of the magnetic field intensity ELF (Extremely Low Frequency) is essentially an attempt to prevent the impact of disease risks posed by electromagnetic field radiation. Measuring instrument used to measure the magnetic field intensity EMF 827 is capable of measuring magnetic fields up to 2000 μT. The results of the intensity of exposure to magnetic fields measured by variations in distance of 20, 40, 60, 80 and 100 cm. The distance is selected because the distance is the distance that allows direct interaction with the magnetic field source. Issues to be studied are comparative intensity of the magnetic field around the electronic equipment with natural magnetic field and the magnetic field distribution around the electronic equipment with a power ≥ 1000 W. Results of comparative data are analyzed using One-Way ANOVA aided by SPSS 23 and presented in the profile / contour Surfer application assisted version 11. Keywords: Analysis of the magnetic field intensity ELF, EMF 827, One-Way Anova, profile / contour,Surfer application assisted